Recurrence of a 30-years old leukemic clone ten years after allogeneic transplant: Azacitidine and donor lymphocyte infusion are an effective strategy to restore the graft-versus leukemia effect. Issue 4 (2019) - Iovino, L; Mazziotta, F; Buda, G; Orciuolo, E; Caracciolo, F; Cecconi, N
No abstract available